Anti-Inflammatory Effects of Ripe Areca Nut Ethyl Acetate Fraction in Wistar Rats with Knee Joints Osteoarthritis - Daffa Akrama Yuda; Ave Olivia Rahman; Fathnur Sani Kasmadi; Humaryanto Humaryanto (Jurnal Kedokteran Brawijaya, 2023)
Osteoarthritis (OA) is the most common form of arthritis. Meloxicam are one of NSAIDs commonly used that have many side effects. Areca nut (Areca catechu L), which contains flavonoids, can provide anti-inflammatory effects. This study aimed to determine the potential anti-inflammatory effect of ethyl acetate fraction from ripe areca nut in OA rat model. Twenty five of adults, male Rattus novergicus strain Wistar were induced to OA with Monosodium Iodoacetate (MIA), then divided into five groups that each group were given ethyl acetate fraction of ripe areca nut doses of 15mg/kgBW, 30mg/kgBW, and 60mg/kgBW, meloxicam 1.35mg/kgBW and aquadest as negative control for 14 days. Diameter of the knee joint is measured by digital metric kaliper to assess joint edema. The Histopathological examination with Haematoxyllin-Eosin stain to assess degree of inflammation on synovial. Among the areca groups, dose 30mg/kgBW had knee joint diameter reduced better and lower synovitis score. In conclusion, ethyl acetate fraction of the ripe areca nut group has anti inflammation effect in OA model but not dose-dependent.